HAK PERLINDUNGAN SOSIAL BAGI LANJUT USIA MENURUT UNDANG-UNDANG NOMOR 13 TAHUN 1998 DAN HUKUM ISLAM DI KECAMATAN MEDAN AMPLAS - Uswatun Hasanah (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2021)
Elderly is a natural and continuous process that undergoes anatomical, physiological, biochemical changes in tissues or the organs which ultimately affects the state of function and the ability of the body as a whole. The Republic of Indonesia has an obligation to prosper the elderly by providing social protection for its people. This is evidenced by the existence of a special law related to the welfare of the elderly, namely the Law no. 13 of 1998.How are the social protection rights for the elderly in Medan Amplas sub-district according to the Law Number 13 of 1998, How are the social protection rights for the elderly in Medan Amplas sub-district according to the Islamic law, how are the similarities and the differences in social protection rights for the elderly in Medan Amplas sub-district according to the Law No. 13 of 1998 and the Islamic Law.The Implementation of the Law no. 13 of 1998 regarding social protection rights for the elderly in Medan Amplas Sub-district is not in line with the Law no. 13 of 1998 or not implemented properly or not optimally implemented in Medan Amplas Sub-district. This is evidenced by the large number of elderly people whose rights are not fulfilled, including their social protection rights. According to the Islamic Law, the Social Protection Rights for the Elderly in Medan Amplas Sub-district is not in line with the Islamic Law. There are still many elderly people who do not receive assistance and the assistance received by the elderly is not evenly distributed. Even Muslim institutions that are specifically for distributing aid to the elderly or the poor are also less effective in promoting the welfare of the elderly. The similarities between the law and the Islamic law related to the social protection rights for the elderly are that they both have special institutions that oversee the social protection rights of the elderly, are both the responsibility of the state and both meet the needs of the elderly. The most prominent difference is the existence of standard rules from the law, whereas in Islam there are no written standard rules.Keywords : Social Protection Rights, Elderly, The Law on Social Protection for the Elderly, Social Protection for the Elderly According to the Islamic Law.